Iron bioavailability from maize and beans: a comparison of human measurements with Caco-2 cell and algorithm predictions - Beiseigel, J.M.; Hunt, J.R.; Glahn, Raymond P.; Welch, R.M.; Menkir, A.; Maziya-Dixon, B.B. (2007)
Background: An in vitro digestion and Caco-2 cell model may predict iron bioavailability to humans; however, direct comparisons are lacking.